Electrocortical Sources Related to Whole-Body Surface Translations during a Single- and Dual-Task Paradigm - Bogost, Mark D.; Burgos, Pablo I.; Little, C. Elaine; Woollacott, Marjorie H.; Dalton, Brian H. (Frontiers in Human Neuroscience, 2016)
Appropriate reactive motor responses are essential in maintaining upright balance. However, little is known regarding the potential location of cortical sources that are related to the onset of a perturbation during single- and dual-task paradigms. The purpose of this study was to estimate the location of cortical sources in response to a whole-body surface translation and whether diverted attention decreases the N1 event-related potential (ERP) amplitude related to a postural perturbation. This study utilized high-resolution electroencephalography in conjunction with measure projection analysis from ERPs time-locked to backwards surface translation onsets to determine which cortical sources were related to whole-body postural perturbations. Subjects (n = 15) either reacted to whole-body surface translations with (dual task) or without (single task) performing a visual working memory task. For the single task, four domains were identified that were mainly localized within the frontal and parietal lobes and included sources from the prefrontal, premotor, primary and supplementary motor, somatosensory, and anterior cingulate cortex. Five domains were estimated for the dual task and also included sources within the frontal and parietal lobes, but the sources also shifted to other locations that included areas within the temporal and occipital lobes. Additionally, mean absolute N1 ERP amplitudes representing the activity from similar locations in both tasks were greater for the single than dual task. The present localization results highlight the importance of frontal, parietal and anterior cingulate cortical areas in reactive postural control and suggest a re-allocation or shift of cortical sources related to reactive balance control in the presence of a secondary task. Thus, this study provides novel insight into the underlying neurophysiology and contribution of cortical sources in relation to the neural control of reactive balance.